C12-02 Leaching Of Massive Sulfide Samples From The Southern Juan De Fuca Ridge, North Pacific Ocean - D. L. Sawyer (The National Institute for Occupational Safety and Health (NIOSH), 1983)
Aqueous C12-02 leaching procedures developed by the Bureau of Mines to produce zinc chloride from zinc sulfide bulk concentrates were effective in extracting 99 pct of the zinc and 97 pet of the silver contained in samples of massive seafloor sulfides from the southern Juan de Fuca Ridge. Zinc sulfide (sphalerite and wurtzite) mineralization comprised 55 and 88 pct of two specimens provided by the U.S. Geological Survey for this study. Minor occurrences of galena, chalcopyrite, and other minerals in the sulfides permitted the recovery of pregnant liquors that were low in metal values other than zinc, which were successfully purified by a two-step cementation procedure using zinc dust.